PARSE PROBLEMS IN THE APPLICATION OF ACCOUNTING BASED IMFI GRAMEEN - Utami, Tri; Afriadi, Fiqih (Universitas Pamulang, 2020)
The purpose of this study is to reveal various problems application of accounting on Islamic Micro Finance Institutions (IMFI) based grameen. To achieve the study researchers used a methodology Analytical Network Process. Decomposition of the problem conducted by survey-based Grameen IMFI to practitioners as well as in-depth interviews to experts or academicians. Based on the results of the study (decomposition problem) suggests that the problems in the application of accounting-based Grameen IMFI divided into three main clusters, namely the lack of regulation of supporting institutions, the absence of operational standards and minimum operational assistance. The finding of the study suggested that the main problem was on the lack of regulation supporting with the priority number (0.31), followed by problems of lack of operational standards (0.28), and finally the lack of operational assistance (0.14)